Analisis Eksistensi Bisnis Islam Di Era Disrupsi 4.0: Studi Takhrij dan Syarah Hadits Pendekatan Hukum Ekomomi Islam - Muhamad Fahrul Maulana; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss takhrij and syarah hadith related to the existence of business in the 4.0 era. This study uses a qualitative approach that emphasizes literature review through the takhrij and syarah hadith methods with contemporary analysis. The results of this study indicate that the hadith narrated by Imam al-Bukhari no. 1930 is closely related to the existence of business in the 4.0 era. The status of this hadith is authentic because it meets the criteria for the authenticity of the sanad and the matan of the hadith. This hadith is considered authentic because all the narrators are dabit and fair (tsiqat). While the hadith syarah shows that business is an activity carried out by humans to earn income and meet the needs of life, so the existence of business must be strengthened and developed by utilizing advances in digital information technology according to the demands of the industrial revolution era 4.0. This study concludes that the hadith narrated by Imam al-Bukhari No. 1930 is acceptable (maqbul) so that it can be used as evidence for the practice of Islam in the context of strengthening the existence and development of business in the midst of the era of disruption 4.0.